Enhancing knowledge and self-care behavior of heart failure patients by interactive educational board game - Anong Amaritakomol (2019)
© 2019 Mary Ann Liebert, Inc., publishers. Objective: To evaluate the effects of an educational board game on heart failure (HF) patients' knowledge and self-care behavior. Methods: In this randomized controlled study with a follow-up of 3 months, 76 patients with HF with reduced ejection fraction, who had been enrolled in our multidisciplinary HF program, were divided into two groups. During their follow-up appointment at the HF clinic usually 2 weeks after discharge, the interventional group participated in an HF educational board game conducted in Thai language, while the control group received the usual care including standard education. The primary outcome was the change of score achieved in the specialized HF knowledge and self-care behavior assessment. Results: In the intervention group, the knowledge and self-care behavior significantly improved (all P < 0.001), whereas both scores were unchanged in the control group (P = 0.09 and P = 0.21). Mean score change for knowledge and self-care behavior showed greater improvement in the intervention group when compared with the control group (P < 0.002 and P < 0.006). Conclusion: Participation in an interactive educational board game resulted in an increase in the HF patients' knowledge and self-care behavior. Practice Implications: An interactive educational board game may be used as an alternative educational tool in HF patients.